Legal Defiance: Government-Sanctioned Graffiti Walls and the First Amendment - Kelly Oeltjenbruns (Washington University Law Review, 2018)
The caricature face of Maine Governor Paul LePage, wearing a Ku Klux Klan hood and surrounded by the words homophobe, moron, and racist greeted every passerby of the Portland Water District (PWD) in Portland, Maine on September 6, 2016. The image sparked a controversial exchange between local government entities, a rarity since the City of Portland and PWD agreed to provide the hundred-foot wall as a public graffiti site in 2001. City spokeswoman Jessica Grondin said the city “can’t do anything because [the graffiti is] sanctioned and it’s a matter of free speech.” Mayor Ethan Strimling apparently disagreed and asked PWD to paint over the mural, as “equating the governor and his rhetoric [with the KKK] . . . is a step too far.” Grondin said PWD would not comply with the Mayor’s request, though PWD did not condone the message. Shortly after the mayor called for removal, an unknown party replaced LePage’s hood with Mickey Mouse ears, momentarily assuaging Portland’s free speech tension. But the vigilante Mickey artist merely postponed confronting the issue, as some in Portland called for the PWD to end its allowance for public art. This presents a familiar question in an unfamiliar context: when the government, at any level, creates a space for artists to paint graffiti without prior design approval, how can––and should––the government censor what is painted on those spaces? This Note examines that question. Part I discusses a brief history of graffiti and its proliferation in American culture. Part II highlights the issue of government-sanctioned walls and addresses why there has been little, if any, judicial discussion on government regulation of these spaces, despite the prevalence of graffiti in American television, film, clothing, and other industries. Part III hypothesizes as to which legal doctrines would be relevant to a First Amendment or other challenge to government regulation of graffiti walls and argues that courts should consider a legal graffiti wall to be a designated public forum, with all regulations subject to strict scrutiny. Because there is little opportunity for artists themselves to challenge government censorship of legal walls, the government must also exercise self-restraint if it opts to provide these legal walls. Part IV outlines the considerations a government must consider when creating and maintaining a legal graffiti space to facilitate a more robust public discourse.
Keywords: Graffiti; Free speech; First amendment; Legal graffiti; Public discourse